The Effect of Implementing Green Accounting and CSR On Profitability in Manufacturing Companies Listed on IDX: JEL Classification: M41, Q56, G30, M14 - Nurhasanah, Lulu; Astriani, Devi; Trisyanto, Ade (Newinera Publisher, 2025)
This study aims to determine how the implementation of environmental accounting and CSR will impact the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This study applies a quantitative method, and the sample consists of twenty manufacturing companies selected using a purposive sampling method for five years, a total of 100 observations were generated. The research data were taken from the organization's annual report. The findings of the study indicate that green accounting has a significant impact on the level of profitability as measured by return on assets (ROA). In addition, CSR also has a positive impact on profitability, where companies that are active in CSR activities tend to gain a higher level of trust from stakeholders, thus having a positive impact on financial performance. The conclusion of the study confirms that the simultaneous implementation of Green Accounting and CSR can create strong synergy in increasing the profitability and competitiveness of the company. The implications of this study indicate that companies need to pay more attention to the implementation of Green Accounting and CSR as elements in their business planning.